Hospitalizations for ambulatory care sensitive conditions and unplanned readmissions among Medicare beneficiaries with Alzheimer's disease. Issue 10 (5th September 2017) - Lin, Pei‐Jung; Zhong, Yue; Fillit, Howard M.; Cohen, Joshua T.; Neumann, Peter J.
Abstract: Introduction: Medicare beneficiaries with Alzheimer's disease and related dementias (ADRDs) may have more potentially avoidable hospitalizations and readmissions than people without dementia. These hospitalizations may be indicative of access barriers, problems in continuity of care, inefficient resource use, and poor patient outcomes. Methods: We examined national frequency and costs of ambulatory care sensitive condition hospitalizations and unplanned, all‐cause, and condition‐specific 30‐day readmissions in >2.7 million fee‐for‐service ADRD patients using 2013 Medicare claims data. Results: In 2013, 410, 000 Medicare ADRD patients had ambulatory care sensitive condition hospitalizations or unplanned 30‐day readmissions costing $4.7 billion. One in 10 ADRD patients were hospitalized for a potentially avoidable condition. Almost one in five hospitalized ADRD patients had an unplanned 30‐day readmission. Readmission rates were highest among ADRD patients initially hospitalized for heart failure (22%) and chronic obstructive pulmonary disease (21%). Discussion: Our findings may suggest potential deficiencies in ambulatory care and postdischarge care related to managing comorbidities among Medicare fee‐for‐service ADRD patients.